PENGGUNAAN MEDIA KOMIK DALAM PEMBELAJARAN PAI UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA - Paridah, Idah; Winarti, Wiwin (Prodi PAI IAILM Suryalaya, 2022)
Islamic Education is very important to learn in school. However, if there are other factors that are less supportive, the learning objectives of islamic education in schools are not achieved. For example the lack of untilization and optimization of the use of learning media. Therefore learning activities are always closely related to the process of interaction activities between students as learning parties and teachers as teaching parties. This study aims to determine the increase in motivation to learn class XI TB 3 Telkom Tourism Vocational School bandung using comic media. This study uses Classroom Action Research (CAR) while the method is used observation and written test which is carried out twice the CAR cycle using comic media on the Islamic Glory Period material, in the first cycle the results of students who completed are 20 or 77% and 6 or 23% of students who have not yet completed. Then we can increase in the initial data of 15% and an increase in cycle i gained 38% and cycle II gained 77% with an increase of 39% so that CAR using comic media in increasing student motivation was declared successful. This research has implications for teachers and students. So the students are not bored in the learning process, easier to understand the material, and become motivated in learning islamic education and for teachers to make teachers easier to teach, more interesting and effective.